OKRs for all : making objectives and key results work across your organization - Vellore, Vetri (Ascent Audio, 2023)
The spiritual successor to KPIs (key performance indicators), OKRs, or objectives and key results, are rapidly gaining popularity and helping some of the world's most successful businesses solve their strategic execution problems. However, some companies struggle with their implementation, finding that using OKRs as top-down directives changes little. In OKRs for All, Objectives and Key Results (OKR) expert Vetri Vellore delivers an impactful and actionable guide on how to use OKRs for more than a quarterly, executive-level review tool. You'll discover how to roll out an OKR system that closes the gap between strategy and project, and starts at the bottom of your organization and helps managers and teams organize their daily decisions around shared and important goals. You'll find: a seven-part blueprint and framework to strategically put purpose at the center of your work, whether you are a CX, team lead, or individual contributor; how to build an OKR strike team, align your departments, manage your people, and roll out your new strategic OS; valuable and implementable case studies from companies you know and love; and best practices to follow and common pitfalls and mistakes to avoid when applying OKRs throughout your organization.